Obtención de nuevo germoplasma en Cenchrus ciliaris L. a través de mutaciones inducidas y selección in vitro - Lopez Colomba, Eliana (2011)
Cenchrus ciliaris L., a forage grass of wide distribution in the north-west of Argentina, is a tetraploid (4x = 36) and obligate apomictic species. One way of obtaining novel germplasm is by induced mutations. In this work, physical and chemical mutations are combined with in vitro selection procedures seeking for new germplasm, with emphasis on salinity and drought tolerance. Mature seeds of Cenchrus ciliaris L. cv Biloela were subjected to treatments with X rays (400 Gy) and ethyl methanesulphonate (EMS) water solution (5.5 mM for 24 h). To perform in vitro selection, after 7 days of EMS or X rays treatments, germinated seeds were transferred to tubes containing Murashige and Skoog medium supplemented with NaCl or mannitol to simulate salinity and drought conditions, respectively. Fifty-four selected plants were isolated which tolerated 200 mM NaCl and 100 mM mannitol. Both mutagenic agents exhibited similar percentages of induced genetic variation measured through RAPD polymorphisms. This work demonstrated that genetic variability can be generated in Cenchrus ciliaris L. using mutagenic agents and in vitro selection.